The human DEAD-box helicase DDX3X as a regulator of mRNA translation - Ryan, Cathal S.; Schröder, Martina (Frontiers in Cell and Developmental Biology, 2022)
The human DEAD-box protein DDX3X is an RNA remodelling enzyme that has been implicated in various aspects of RNA metabolism. In addition, like many DEAD-box proteins, it has non-conventional functions that are independent of its enzymatic activity, e.g., DDX3X acts as an adaptor molecule in innate immune signalling pathways. DDX3X has been linked to several human diseases. For example, somatic mutations in DDX3X were identified in various human cancers, and de novo germline mutations cause a neurodevelopmental condition now termed ‘DDX3X syndrome’. DDX3X is also an important host factor in many different viral infections, where it can have pro-or anti-viral effects depending on the specific virus. The regulation of translation initiation for specific mRNA transcripts is likely a central cellular function of DDX3X, yet many questions regarding its exact targets and mechanisms of action remain unanswered. In this review, we explore the current knowledge about DDX3X’s physiological RNA targets and summarise its interactions with the translation machinery. A role for DDX3X in translational reprogramming during cellular stress is emerging, where it may be involved in the regulation of stress granule formation and in mediating non-canonical translation initiation. Finally, we also discuss the role of DDX3X-mediated translation regulation during viral infections. Dysregulation of DDX3X’s function in mRNA translation likely contributes to its involvement in disease pathophysiology. Thus, a better understanding of its exact mechanisms for regulating translation of specific mRNA targets is important, so that we can potentially develop therapeutic strategies for overcoming the negative effects of its dysregulation.